Studi Empiris Customer Relationship Management (CRM) Citra Merek dan Kepuasan terhadap Loyalitas Pelanggan The Body Shop Jember - Diwan Sakharia; Retno Endah Supeni; Achmad Hasan Hafidzi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to understand and analyze to test and analyze the significant influence of CRM, brand image, and satisfaction on customer loyalty at The Body Shop Jember. Primary data includes data on filling out questionnaires, interviews and observations of customer loyalty at The Body Shop Jember. While secondary data includes references derived from books, scientific articles, and the internet. Primary data and secondary data are the types of data used for this study. Based on the results of the analysis, it shows that customer loyalty at The Body Shop Jember based on aspects of CRM, brand image, and satisfaction is classified as very influential. As for several aspects that have an impact on the level of customer loyalty at The Body Shop Jember in 2022-2023, the results of this study state that CRM, brand image, and satisfaction have a significant effect on customer loyalty at The Body Shop Jember.